Interaction of discourse processing impairments, communicative participation, and verbal executive functions in people with chronic traumatic brain injury - Büttner-Kunert, Julia; Blöchinger, Sarah; Falkowska, Zofia; Rieger, Theresa; Oslmeier, Charlotte (Frontiers in Psychology, 2022)
Especially in the chronic phase, individuals with TBI (IwTBI) may still have impairments at the discourse level, even if these remain undetected by conventional aphasia tests. As a consequence, IwTBI may be impaired in conversational behavior and disadvantaged in their socio-communicative participation. Even though handling discourse is thought to be a basic requirement for participation and quality of life, only a handful of test procedures assessing discourse disorders have been developed so far. The MAKRO Screening is a recently developed screening tool designed to assess discourse impairments. The aim of our study was to investigate discourse processing in IwTBI in different tasks and to assess problems in communicative participation in the post-acute and chronic phase. In this context, we also aimed to analyze the influence of the severity of the initial impairment and the verbal executive abilities on the discourse performance. Additionally, the impact of macrolinguistic discourse impairments and verbal fluency on perceived communicative participation was targeted in our analysis. To date, Data from 23 IwTBI (moderate to severe) and 45 23 healthy control subjects have been analyzed. They completed two subtests of the MAKRO screening: Text production and Inferences. Discourse performance was examined in relation to measures of semantic fluency and verbal task-switching. Socio-communicative problems were evaluated with the German version of the La Trobe Communication Questionnaire (LCQ) Results: IwTBI showed lower test results than the control group in all the two subtests of the MAKRO-Screening. Difficulties in picture-based narrative text production also indicated greater perceived difficulties in communicative participation (LCQ). We also found that the subject’s performance on the MAKRO-Screening subtests can partly be explained by underlying dysexecutive symptoms (in terms of verbal fluency and verbal task switching) and the severity of their injury. The preliminary results of our study show that cognitive-linguistic symptoms in IwTBI are also evident in the chronic phase. These can be detected with procedures referring to the discourse level, such as the MAKRO-Screening. The assessment of discourse performance should be an integral part in the rehabilitation of IwTBI in order to detect cognitive-linguistic communication disorders and to evaluate their impact on socio-communicative participation.